Antiviral Activity of Cytovir®-3 Against Human Rotavirus Infection Agent in vitro - E. B. Faizuloev; I. A. Leneva; V. S. Smirnov; D. I. Smirnova; A. V. Gracheva; E. R. Korchevaya; D. M. Khokhlova; T. A. Kudryavtseva; S. V. Petlenko; V. A. Zaplutanov (Антибиотики и Химиотерапия, 2024)
Introduction. Rotavirus infection causes more than 250 million episodes of acute gastroenteritis annually, of which approximately 130,000 cases in children under 5 years of age are fatal. In this regard, the search for drugs for the treatment of rotavirus infection seems extremely relevant.The aim of the research was to evaluate the antiviral activity of Cytovir®-3 against human rotavirus on a cellular infection model.Material and methods. The objects of the study were a mixture of active ingredients and individual components, identical in composition and ratio, contained in Cytovir®-3. The study was carried out using a monkey kidney cell culture MA-104 and a laboratory strain of human group A rotavirus — 568, genotype G3P. Cultural, virological, molecular biological and statistical methods were used during the study.Results and discussion. Analysis of the survival of MA-104 cells in the presence of Cytovir®-3 showed that in the concentration range from 100 to 200 µg/ml, the drug reproducibly exhibited antiviral activity, which was expressed in increased cell survival compared to the viral control. Cytovir®-3 in a non-toxic concentration of 150 µg/ml suppressed the reproduction of rotavirus by 1.0-2.0 lg СC₅₀/ml with various schemes of introduction into cell culture at all periods of observation, which was accompanied by a significant decrease in the concentration of viral RNA and a cytoprotective effect.